Genome-wide gene expression profiling of homeodomain-interacting protein kinase 2 deficient medullary thymic epithelial cells - Rattay, Kristin (Genom Data, 2015)
The establishment of central tolerance essentially depends on the promiscuous gene expression (pGE) of a plethora of tissue restricted antigens by the medullary thymic epithelial cells. The antigens are presented to developing thymocytes in the thymus to select for non-self reactive T-cell receptors in order to prevent autoimmune reactions in the periphery. However the molecular regulation of tissue-restricted antigen expression is still poorly understood. The only regulator known to play a role in the transcriptional regulation so far is the autoimmune regulator (AIRE). AIRE is thought to act in a multi-protein complex, promoting transcription, elongation and splicing of target genes. Yet the full composition of this Aire-associated multi-protein complex and its mode of action remain to be elucidated. Here we describe the experimental details and controls of the gene array analysis on the impact of the homeodomain-interacting protein kinase 2 (Hipk2) on promiscuous gene expression in medullary thymic epithelial cells based on the analysis of newly generated TEC-specific Hipk2 conditional knockout mice. The changes in gene expression are presumably mediated through a regulatory effect of Hipk2 on AIRE as published in the study by Rattay and colleagues in the Journal of Immunology [1]. The gene array data reported in this paper have been deposited in the Gene Expression Omnibus (GEO) database, www.ncbi.nlm.nih.gov/geo (accession no. GSE63432).